Скоростная модель строения мантии под о-вом Суматра и сейсмичность района - Кендзера, А.В.; Заец, Л.Н.; Цветкова, Т.А.; Островной, А.Н. (Геофизический журнал, 2014)
У межах побудованої тривимірної ⵼-швидкісної моделі мантії Південно-Східної Азії розглянуто швидкісну будова мантії під о-вом Суматра та його оточенням з визначенням можливих передумов у глибинній будові мантії для прояву землетрусів у регіоні. Модель отримано в результаті застосування методу тейлорового наближення для розв’язання задачі сейсмічної томографії часів приходу ⵼-хвиль, запропонованого В. С. Гейком. Within the framework of a three-dimensional P-velocity model of the mantle of the South-East Asia, the mantle velocity structure beneath Sumatra and its surroundings has been considered with the identification of possible premises in the deep structure of the mantle for manifestation of earthquakes in the region. The model has been obtained by application of the method of Taylor approximation for solution of seismic tomography problem of P-waves arrival time introduced by V.S. Geiko.